The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1590/s0102-09352004000100019
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos clínicos e de laboratório de cães soropositivos para leishmaniose

Abstract: A leishmaniose é uma doença parasitária cujos agentes etiológicos são diferentes espécies de protozoários do gênero Leishmania, que são transmitidos pela picada de dípteros da família Psychodidae, dos gêneros Lutzomyia e Phlebotomus.Dentre as leishmanioses, o tipo visceral é a forma mais grave e é considerada uma zoonose que tem o cão como principal reservatório no ciclo peri-doméstico. Segundo Marzochi et al. (1985), sua ocorrência tem sido registrada em diversos estados do Brasil e também na área do Grande R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
4
0
13

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 6 publications
2
4
0
13
Order By: Relevance
“…These data confirm the clinical findings that have been reported in the literature 15,16 . It is noteworthy that Mattos Jr et al 15 found 88.8% of animals with leishmaniasis presenting more than one clinical sign.…”
Section: Discussionsupporting
confidence: 92%
“…These data confirm the clinical findings that have been reported in the literature 15,16 . It is noteworthy that Mattos Jr et al 15 found 88.8% of animals with leishmaniasis presenting more than one clinical sign.…”
Section: Discussionsupporting
confidence: 92%
“…Reservoirs for the disease include the domestic dog, of major epidemiological importance in maintaining the disease cycle. Various studies 3,5,6 have shown that in some cases canine infection precedes the appearance of human cases, but this finding may reflect dogs' greater susceptibility to the infection. Culling of infected dogs as a prophylactic and control measure is routine in endemic control programs 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…A leishmaniose em cães é uma doença que causa uma discreta anemia do tipo normocítica e normocrômica, conforme já descrito por alguns autores (Ikeda-Garcia et al 2003, Mattos Jr et al 2004, Braz et al 2015, entretanto, não há estudos correlacionando os valores de RDW e VCM com a citometria eritrocitária em cães com leishmaniose visceral.…”
unclassified